Review Writing as Part of the Doctoral Qualification Process in Theses-By-Publication. Results of an Interview Study With Ph.D. Students in German Sports Science - Jaitner, David; Gabriel, Lena; Zander, Benjamin (Frontiers in Education, 2022)
Although review writing is becoming increasingly relevant for theses-by-publication processes, the topic of review writing has hardly been empirically studied from the Ph.D. students' perspective. This paper addresses this desideratum by providing results of an exploratory study on review writing in German sports science. Based on a social constructivist approach and a socialization theory frame, the study investigated complexes of themes and knowledge that characterize Ph.D. students` review writing as part of sports science doctoral qualification processes within theses-by-publication. Between January and March 2021, 20 Ph.D. students from different sports science subdisciplines were interviewed using expert interviews. A structured-thematic qualitative content analysis identified six main experiential fields of review writing (type of review, individual significance of the review in the doctoral process, approach to writing the review, acquisition of review writing as a method, opportunities in elaborating and publishing the review, and challenges in elaborating and publishing the review). The topics of the category system highlight the diversity of review writing experiences, which can be bundled as content-related, social and affective dimensions of socialization processes. At the same time, the topics of the category system allow to specify three dimensions of the socialization process for (sports) scientific qualification processes. In this way, the perspective of Ph.D. students on review writing as a central scientific practice and part of the doctoral dissertation is fundamentally determined. This could represent a gain in knowledge for the future implementation of research projects on the doctoral culture within as well as outside of sports science.